Cancer and cardiovascular disease: The impact of cardiac rehabilitation and cardiorespiratory fitness on survival - Williamson, Tamara; Moran, Chelsea; Chirico, Daniele; Arena, Ross; Ozemek, Cemal; Aggarwal, Sandeep; Campbell, Tavis; Laddu, Deepika (International journal of cardiology, 2021)
Cancer survivors are at increased risk for cardiovascular disease (CVD)-related morbidity and mortality. Exercise-based cardiac rehabilitation (CR) programs improve CVD risk factors, including cardiorespiratory fitness (CRF). The purpose of this study was to investigate: (1) the association between CR completion and survival, and (2) whether CRF improvements translate to increased survival among patients with comorbid cancer and CVD. Patients with CVD and pre-existing cancer (any type) were referred to a 12-week exercise-based CR program between 01/1996 and 03/2016. Peak metabolic equivalents (METs) were assessed by graded exercise test pre-CR and at 12-weeks. Kaplan-Meier survival and multivariate cox regressions were performed to evaluate impact of CR completion and clinically-meaningful CRF improvements [ΔMETs≥1] on survival, adjusting for relevant covariates. Among 442 patients with CVD and cancer referred to CR (67 ± 10 years; 22% women), 361 (82%) completed CR. 102 deaths were recorded during the 12-year observation period. Compared to patients who did not complete CR, patients with comorbid cancer who completed CR demonstrated a survival advantage (63% vs 80.1%, p < .001). CRF improved among completers during the 12-week program (mean change = 0.87 ± 0.93 METs, p < .001); 41% experienced a clinically-meaningful ΔMETs≥1. A survival advantage was not observed in completers who experienced a ΔMETs≥1 improvement (p = .254). Completing a 12-week exercise-based CR program improved CRF and increased survival in patients with CVD and comorbid cancer. The results highlight the survival benefits of completing a CR program among CVD patients who experience added barriers imposed by cancer treatment and survival. •Cancer predisposes individuals to cardiovascular disease (CVD)-related illness and death.•Exercise-based cardiac rehabilitation improved cardiorespiratory fitness in patients with CVD and cancer.•Cardiac rehabilitation completion improved survival in patients with CVD and cancer.